2016
DOI: 10.2106/jbjs.15.01093
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Low-Energy Basicervical Proximal Femoral Fractures Treated with Cephalomedullary Fixation

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 20 publications
2
100
1
9
Order By: Relevance
“…The basicervical fracture line is the most significant feature of this cohort of patients. Strictly, a basicervical fracture is defined as a 2-part fracture where the fracture line originates from the base of the femoral neck and exits above the lesser trochanter [9]. Despite the concomitant PLF or LT fracture, the primary fracture lines in this cohort of patients met this description exactly.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The basicervical fracture line is the most significant feature of this cohort of patients. Strictly, a basicervical fracture is defined as a 2-part fracture where the fracture line originates from the base of the femoral neck and exits above the lesser trochanter [9]. Despite the concomitant PLF or LT fracture, the primary fracture lines in this cohort of patients met this description exactly.…”
Section: Discussionmentioning
confidence: 89%
“…There is little controversy about the fact that a basicervical fracture is an unstable fracture and prone to varus deformity [10]. Sliding screws were initially proposed as a treatment for these fractures [11,12], but the recent trend favors IN fixation [9,13]. Anatomically, the piriformis fossa is the transitional region between the hard cortex of the femoral neck and the relatively weak cancellous bone of the GT [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, neckshaft malreduction was another modifiable significant risk factor for cephalomedullary nail cutout in the treatment of trochanteric fractures [23]. Especially, these increased failure rates in helical blade use have been shown in the basicervical femoral neck fractures [22,24], although no single explanation for atypical cutout has been confirmed. The authors advocated the importance of fracture reduction in mitigating medial migration [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported better results with the use of SHS in intertrochanteric fracture treatment and others have stated that CMN give better results (6)(7)(8). However, the current approach to the treatment of unstable intertrochanteric fractures is the use of CMN (9)(10)(11). It has been reported that basicervical fractures could also be evaluated as unstable fractures (12).…”
Section: Introductionmentioning
confidence: 99%